Kelola Emosi Berbasis Experiential Learning dalam Mengembangkan Kelas Bernuansa Social Emotional Learning: Managing Emotions Based on Experiential Learning in Developing Classes with a Social Emotional Learning Nuance - Desti Mahardikawati; Dyah Lyesmaya; Wiwin Winarni (ITScience (Information Technology and Science), 2026)
This Community Service (PkM) activity aims to improve teachers' understanding and skills in managing emotions and implementing Social Emotional Learning (SEL) in the school environment. The program is motivated by the results of a needs diagnosis through interviews with the principals of partner schools, namely SMP Plus Luqmanulhakim, RA Luqmanulhakim, SDN Lebaklarang, and SDN Nyangkowek 2, which showed that teachers needed to strengthen their guidance competencies, especially in the social and emotional aspects of students, amidst limited Guidance and Counseling (BK) services in schools. The needs diagnosis was carried out using the VTS Pedagogy (Visualize Thinking Strategies) approach. The PkM program was implemented through an Emotion Management workshop with an Experiential Learning approach (Kolb, 2015) through the ARKA method (Activity, Reflection, Conceptualization, and Application). The subjects of the activity were RA, elementary, and junior high school teachers from four partner schools. The results of the activity showed an increase in teachers' understanding of emotional regulation and SEL based on a comparison of pre-test and post-test results, an increase in teachers' ability to recognize students' emotional states, and the production of simple media in the form of an Emotional Weather Board, an Emotional Choice Wheel, and an Emoticon Tracker that can be used in learning. Participant reflections showed that the training was interactive, easy to understand, and motivated teachers to apply the training results in the classroom. This activity has implications for strengthening teachers' competencies to create more humanistic and nuanced Social-Emotional Learning (SEL).